Indirect neonatal hyperbilirubinemia in hospitalized neonates on the Thai-Myanmar border: a review of neonatal medical records from 2009 to 2014 - L. Thielemans; M. Trip-Hoving; J. Landier; C. Turner; T. J. Prins; E. M. N. Wouda; B. Hanboonkunupakarn; C. Po; C. Beau; M. Mu; T. Hannay; F. Nosten; et al. (BMC, 2018)
Abstract Background Indirect neonatal hyperbilirubinemia (INH) is a common neonatal disorder worldwide which can remain benign if prompt management is available. However there is a higher morbidity and mortality risk in settings with limited access to diagnosis and care. The manuscript describes the characteristics of neonates with INH, the burden of severe INH and identifies factors associated with severity in a resource-constrained setting. Methods We conducted a retrospective evaluation of anonymized records of neonates hospitalized on the Thai-Myanmar border. INH was defined according to the National Institute for Health and Care Excellence guidelines as 'moderate' if at least one serum bilirubin (SBR) value exceeded the phototherapy threshold and as 'severe' if above the exchange transfusion threshold. Results Out of 2980 records reviewed, 1580 (53%) had INH within the first 14 days of life. INH was moderate in 87% (1368/1580) and severe in 13% (212/1580). From 2009 to 2011, the proportion of severe INH decreased from 37 to 15% and the mortality dropped from 10% (8/82) to 2% (7/449) coinciding with the implementation of standardized guidelines and light-emitting diode (LED) phototherapy. Severe INH was associated with: prematurity (< 32 weeks, Adjusted Odds Ratio (AOR) 3.3; 95% CI 1.6-6.6 and 32 to 37 weeks, AOR 2.2; 95% CI 1.6-3.1), Glucose-6-phosphate dehydrogenase deficiency (G6PD) (AOR 2.3; 95% CI 1.6-3.3), potential ABO incompatibility (AOR 1.5; 95% CI 1.0-2.2) and late presentation (AOR 1.8; 95% CI 1.3-2.6). The risk of developing severe INH and INH-related mortality significantly increased with each additional risk factor. Conclusion INH is an important cause of neonatal hospitalization on the Thai-Myanmar border. Risk factors for severity were similar to previous reports from Asia. Implementing standardized guidelines and appropriate treatment was successful in reducing mortality and severity. Accessing to basic neonatal care including SBR testing, LED phototherapy and G6PD screening can contribute to improve neonatal outcomes.